Detection technology and clinical applications of serum viral products of hepatitis B virus infection - Liu, Ying; Wu, Di; Zhang, Kui; Ren, Rongrong; Liu, Yuxuan; Zhang, Shuya; Zhang, Xuanyu; Cheng, Jilin; Chen, Liping; Huang, Jun (Frontiers in Cellular and Infection Microbiology, 2024)
Viral hepatitis, caused by its etiology, hepatitis virus, is a public health problem globally. Among all infections caused by hepatitis-associated viruses, hepatitis B virus (HBV) infection remains the most serious medical concern. HBV infection particularly affects people in East Asia and Africa, the Mediterranean region, and Eastern Europe, with a prevalence rate of > 2%. Currently, approximately 1 billion people worldwide are infected with HBV, and nearly 30% of them experience chronic infection. Chronic HBV infection can lead to chronic hepatitis B (CHB), liver cirrhosis, and hepatocellular carcinoma (HCC), resulting in the related death of approximately 1 million people annually. Although preventative vaccines and antiviral therapies are currently available, there is no cure for this infection. Clinical testing is not only the gateway for diagnosis of HBV infection, but also crucial for judging the timing of medication, evaluating the effect of antiviral therapy, and predicting the risk of relapse after drug withdrawal in the whole follow-up management of hepatitis B infected persons. With advances in detection technology, it is now possible to measure various viral components in the blood to assess the clinical status of HBV infection. Serum viral products of HBV infection, such as HBV DNA, HBV RNA, hepatitis B surface antigen, hepatitis B e-antigen, and hepatitis B core-related antigen, are non-invasive indicators that are critical for the rapid diagnosis and management of related diseases. Improving the sensitivity of monitoring of these products is essential, and the development of corresponding detection technologies is pivotal in achieving this goal. This review aims to offer valuable insights into CHB infection and references for its effective treatment. We provide a comprehensive and systematic overview of classical and novel methods for detecting HBV serum viral products and discusses their clinical applications, along with the latest research progress in this field.